Transdisciplinary Approach to Risk Analysis in Building Automation and Control System Projects: A Case Study - Namjoo, Mohammad Reza; Salahi, Mehrzad (Transdisciplinary journal of engineering & science, 2025)
Building automation and control systems are kinds of complex systems that face a variety of risks during implementation. The negative consequences of such risks can impact the project execution and success. The origins of the risks associated with BACS implementation in the context of construction projects are diverse and include technical, economic, political, social, and cultural domains. Identifying the risk factors of BACS projects and analyzing causal relationships among them can enable project key stakeholders to define and execute timely response–to-risks strategies. With regard to complex and multifaceted context of risks in BACS projects, this paper uses a transdisciplinary risk analysis approach to identify and rank BACS Projects risk factors along with a causal analysis in a case study. The results of this paper provide comprehensive insights into BACS project risk factors and can be used in real-world projects to design actionable risk mitigation plans.